Chemical reaction analyses based on orbitals and orbital energies. Issue 5 (18th October 2014) - Tsuneda, Takao; Nakai, Hiromi; Tsuneda, Takao
<x xml:space="preserve">Abstract</x> Reaction analysis theories based on molecular orbitals and orbital energies are reviewed based on their histories, formulations, and availabilities. Frontier orbital theory has played a leading role in orbital‐based reaction analyses through the medium of conceptual density functional theory (DFT) called by the name of the Fukui function. Orbital‐based reaction analyses raise the stakes from the experimental viewpoint. However, molecular orbitals are too insensitive to be used in quantitative discussions as symbolized by the fact that several main reactivity indices have recently been questioned. Orbital energies are better suited to quantitative reaction analyses because these are very sensitive to the quality of electron correlation that is included. As orbital energies have recently been accurately reproduced by long‐range corrected DFT, orbital energy‐based theories have also become possible. Although, the Fukui function is not appropriate as an orbital energy‐based reactivity index, the initial orbital energy gap gradient on the intrinsic reaction coordinate may provide a hint to construct theories for orbital energy‐based reaction analysis. © 2014 Wiley Periodicals, Inc.